An atypical teratoid/rhabdoid tumor (AT/RT) with molecular features of pleomorphic xanthoastrocytoma (PXA) in a 62-year-old patient - Matthias Dottermusch (University of Münster / Open Journals System, 2021)
Atypical teratoid/rhabdoid tumors (AT/RT) are aggressively growing malignant embryonal neoplasms of the central nervous system (CNS), which mainly affect young children. Loss of SMARCB1/INI1 (or SMARCA4 in rare cases) is recognized as the genetic hallmark of AT/RTs and these tumors can be distinguished into three distinct DNA-methylation based molecular subgroups (i.e. -MYC, -SHH and -TYR). While most AT/RTs are considered to occur de novo, previous studies have recognized secondary SMARCB1/INI1-deficient rhabdoid tumors arising from other low grade CNS tumors in young patients. Three AT/RTs, which harbor epigenetic and mutational characteristics of pleomorphic xanthoastrocytoma (PXA), while being entirely void of nuclear SMARCB1/INI1 expression, were recently described in older children. We here report the first case of an AT/RT with molecular features of PXA in a senior patient.